Cluster innovation along the industry lifecycle - Andreas Eisingerich; Oliver Falck; Stephan Heblich; Tobias Kretschmer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Industrial clusters develop regionally along the industry's lifecycle and typically exist over many product generations. In order to maintain their innovativeness, they have to develop and adjust along the industry lifecycle. We conduct 142 depth face-to-face interviews in clusters across two continents to examine the drivers of a cluster's innovativeness along the industry lifecycle. The results from our interviews suggest that the impact of key drivers of cluster innovativeness change depending on the stage of a cluster's underlying industry lifecycle. Classifying clusters as either being adolescent (information technology, biotechnology) or mature (automotive, chemicals), our regression analyses show a changing influence of cluster patterns along the industry lifecycle on a firm's innovativeness. Specifically, we analyze the impact of interorganizational network strength, openness, university collaboration, and intrapreneurship on radical innovation across adolescent and mature clusters. Implications for research and policy makers are discussed.
Keywords: O18; R12; L6; 330; Cluster; industry lifecycle; innovation; Regionale Konzentration; Produktlebenszyklus; Innovation; Branche; Lebenszyklus; Welt